TEACHER’S EFFORTS IN IMPROVING THE STUDENTS’ ENGLISH ABILITY DURING ONLINE LEARNING - Pramesthi, Amanda; Rachmawati , Rina; Priastuti, Dyah Nugraheny (IKIP Widya Darma, 2022)
The purposes of writing this thesis are: (1) To find out the teacher's efforts in improving students' English skills through the online process and (2) To find out how the students result from the efforts given by the teacher in improving English language skills through the online process. In this study, the researchers used: The method used is qualitative. The data were collected using interviews and documentation on English teachers, students, and SMK Kartika 1 Surabaya students. In this study, researchers used two interview methods: structured interview and semi-structured interview. The results of this study can be concluded that the teacher's efforts to improve students' abilities during online learning are through the WhatsApp application in which the teacher creates a WhatsApp chat group so that students can discuss with their friends without internet network constraints. In addition, most students showed a positive impression of the learning method via WhatsApp from those previously using the learning method through moodle e-learning.